Manajemen Pembelajaran Berbasis Outing Class di MTs Tahfidzul Qur'an Azhar Center Makassar - Ayyasy, Muhammad; Wahira; Ardiansyah, Muhammad (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to describe outing class-based learning management at MTs Tahfidzul Qur'an Azhar Center Makassar, including planning, implementation, evaluation, as well as supporting and inhibiting factors. This study uses a qualitative approach with a descriptive research type. Data collection techniques were carried out through interviews, observations, and documentation with key informants, namely the head of the madrasah, teachers, activity committees, and students. The results show that outing class-based learning is managed systematically and collaboratively through two main activities, namely Literacy and Creativity Camp and Ramadan Celebration. Activity planning is carried out by determining the objectives, materials, methods, media, and schedule in accordance with the characteristics of the students and the vision of the madrasah. The implementation of activities takes place through a briefing stage, core activities based on direct experience, and a closing stage in the form of reflection. Learning evaluation was conducted through student reflection, teacher reports, and evaluation meetings as a basis for program improvement. Factors supporting the activities included teacher involvement, parental support, and the availability of facilities and infrastructure, while inhibiting factors included limited funds and external resource persons.